2014
DOI: 10.1186/2045-3701-4-72
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of IL-25 (IL-17E) confers resistance to dextran sulfate sodium-induced colitis in mice

Abstract: BackgroundIL-25 is emerging as a key regulator of inflammation in the intestinal mucosa because of its ability to promote type 2 while suppressing Th1 and Th17 responses. Several previous studies reported inconsistent results on the role of exogenous IL-25 in development of colonic inflammation and none were performed in animals with a genetic deletion of IL-25. We investigated the contribution of endogenous IL-25 to DSS-induced colitis using mice deficient in IL-25.ResultsMice were exposed to DSS in drinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
2
18
1
Order By: Relevance
“…Consistent with this, when IL-25 −/− mice were used in another model of helminth infection, Nippostrongylus brasiliensis , the protective role of IL-25 was dependent on its ability to induce type-2 cytokine production 32 . Models of colitis have shown IL-25 to be either protective 33 or promoting 34 of inflammation in the gastrointestinal tract. However, when IL-25 −/− mice were used in the colitis associated colon cancer model, we found no difference in the ultimate outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, when IL-25 −/− mice were used in another model of helminth infection, Nippostrongylus brasiliensis , the protective role of IL-25 was dependent on its ability to induce type-2 cytokine production 32 . Models of colitis have shown IL-25 to be either protective 33 or promoting 34 of inflammation in the gastrointestinal tract. However, when IL-25 −/− mice were used in the colitis associated colon cancer model, we found no difference in the ultimate outcome.…”
Section: Discussionmentioning
confidence: 99%
“…144 A recent study showed that IL-17E was produced by intestinal epithelial cells during acute colitis and that mice deficient in IL-17E were protected from DSS-induced colitis. 65,146 Furthermore, neutralizing IL-17E or IL-17RB with antibodies ameliorates the onset of oxazolone-induced colitis. 147 These contradictory results suggest that endogenous IL-17E signaling rather than the exogenous delivery of IL-17E might be pathogenic and contribute to intestinal inflammation.…”
Section: Il-17dmentioning
confidence: 99%
“…IL-17E, also known as IL-25, possesses the lowest homology with IL-17A and is also produced by epithelial cells (Angkasekwinai et al, 2007;Johnston et al, 2013;Xu and Dong, 2017). Although initially thought to exclusively participate in T helper type 2 responses in the gut and lung (Angkasekwinai et al, 2007;Ballantyne et al, 2007;Caruso et al, 2009;Hvid et al, 2011;Owyang et al, 2006;Wang et al, 2014;Xu and Dong, 2017), IL-17E was demonstrated recently to be implicated in several skin inflammatory disorders. In atopic dermatitis, IL-17E was shown to impair the proper epidermal barrier formation (Deleuran et al, 2012;Hvid et al, 2011).…”
Section: Introductionmentioning
confidence: 99%